THE ANALYSIS OF LEVERAGE IN INDONESIA’S FOOD AND BEVERAGE PROCESSING COMPANIES TO THEIR PROFITABILITY - Tahalele, Stevanny Julien Elfiandra; Mekel, Peggy Adeline (FEB Universitas Sam Ratulangi Manado, 2014)
Leverage is a method used by companies to increase their earnings by taking risk in debt, level of fixed asset, and the combination of both. Those methods can affect company’s profitability due to the risk they taken by applying this method. The greater risk company take by using leverage, their expected return should also be greater. The purpose of this research is to create comparison about leverage usage in sample companies and to analyze is there any difference in the profitability of the food and beverage companies after they applied financial leverage, operating leverage, and total leverage to maximize profit. This research used quantitative analysis by one-way Anova. Samples are the six public companies listed in Indonesian Stock Exchange and classified in Indonesia’s food and beverage processing industry. The conclusion is Indofood Sukses Makmur applied highest financial leverage and Charoen Pokphand Indonesia applied highest operating and total leverage. One-way Anova was conducted for financial, operating, and total leverage but shows no significant difference between the sample companies. Although leverage exists and used by company, it is not strong enough to affect company profitability. The management of company should maximize leverage in order to maximize their profit as well. Keywords: financial leverage, operating leverage, total leverage, profitability